The Essence of Social Support, Psychological Well – Being, and Self – Love : A Key to Long – Term Marriage - Endri Yeni Astuti; Rulita Hendriyani (Universitas Malahayati, 2026)
ABSTRACT This study aims to examine the effect of social support, psychological well-being, and self-love on long-term marriage sustainability. A multiple regression analysis was used to test the relationship between the three independent variables and marital sustainability. The results show that social support and psychological well-being have a positive and significant influence on long-term marriage, with p-values below 0.05. This means that people who receive strong support from others and have good mental health are more likely to maintain a stable and lasting marriage. However, self-love does not have a significant effect (p 0.05), suggesting that loving oneself alone may not be enough to keep a marriage strong without mutual care and relationship-focused behavior. The R-squared value of 0.873 indicates that the three variables explain 87.3% of the variation in long-term marriage sustainability. These findings highlight the importance of social and emotional support in building a lasting relationship. Keywords: Marriage Sustainability, Social Support, Psychological Well-Being, Self-Love, Multiple Regression.